Outer membrane vesicles of the oral pathogen Porphyromonas gingivalis promote aggregation and phagocytosis of Staphylococcus aureus - du Teil Espina, Marines; Haider Rubio, Anna; Fu, Yanyan; López-Álvarez, Marina; Gabarrini, Giorgio; van Dijl, Jan Maarten (Frontiers in Oral Health, 2022)
Staphylococcus aureus is an opportunistic Gram-positive bacterial pathogen that causes a wide variety of infectious diseases, including S. aureus bacteremia (SAB). Recent studies showed that rheumatoid arthritis (RA) is a risk factor for SAB, as RA patients appear to be more susceptible to SAB and display higher degrees of disease severity or complications, such as osteoarticular infections. On the other hand, Porphyromonas gingivalis is a Gram-negative bacterial oral pathogen, which is notable for its implication in the etiopathogenesis of RA due to its unique citrullinating enzyme PPAD and its highly effective proteases, known as gingipains. Both PPAD and gingipains are abundant in P. gingivalis outer membrane vesicles (OMVs), which are secreted nanostructures that originate from the outer membrane. Here we show that P. gingivalis OMVs cause the aggregation of S. aureus bacteria in a gingipain- and PPAD-dependent fashion, and that this aggregation phenotype is reversible. Importantly, we also show that the exposure of S. aureus to OMVs of P. gingivalis promotes the staphylococcal internalization by human neutrophils with no detectable neutrophil killing. Altogether, our observations suggest that P. gingivalis can eliminate its potential competitor S. aureus by promoting staphylococcal aggregation and the subsequent internalization by neutrophils. We hypothesize that this phenomenon may have repercussions for the host, since immune cells with internalized bacteria may facilitate bacterial translocation to the blood stream, which could potentially contribute to the association between RA and SAB.